(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Translation is viewed as one of the most central fields of philology and plays a significant role in breaking down language and cultural barriers. This paper discusses the complex art of translation and gives it meaning to users on the importance of the practice in aiding communication and interaction among cultures. It is, therefore, through the in-depth examination of the intricacies and difficulties within the translation process that this paper brings to light a very nuanced interplay among languages, cultures, and the translator as the medium between them. The article tries to place historically, up to the present context, how the complexity of translation and its ensuing impact on issues of philology takes shape.